Oliver Twist Based on the Novel by Charles Dickens - Muri, John (image Entertainment, 2000)
Lon Chaney portrays the frightful, despicable Fagin in this richly atmospheric screen adaptation of Charles Dickens' "Oliver Twist." Jackie Coogan (The Kid) stars as the titular irrepressible waif in 19th-century England, whose adventures lead him from undernourished orphan to undertaker's apprentice, from novice pickpocket to pampered youth. Faithful in spirit and letter to Dickens' immortal story, "Oliver Twist" is an exquisitely designed film, recreating with painterly care the firelit chambers, sepulchral basements and sordid slums that confine its menagerie of eccentric and pathetic personages. [www.jpc.de]